2020
DOI: 10.1108/ijesm-08-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Integration of oil with macroeconomic indicators and policy challenges in regard to Oman

Abstract: Purpose The Oman economy is dominated by production and export of petroleum products and an overdependence on oil revenue, which may have contributed to the continuance of the “resource curse” phenomenon. The purpose of this research is to examine the co-integration of oil with macroeconomic indicators of Oman and of suggesting some policy reform measures to trim down overdependence on oil. Design/methodology/approach The authors culled out data from the annual reports published by the Central Bank of Oman f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The oil price volatility that occur in a country can affect its exchange rate movements (Babatunde, 2015). Oil commodities, including oil prices and oil exports, have proven a strong long-term integration relationship with several variables including time deposits, demand deposits and gross domestic savings (Aravind & Nayar, 2020). High volatility in oil prices tends to be triggered by increased demand that cannot be met by suppliers, resulting in scarcity both in developed markets and emerging markets (Abdelaziz, Chortareas, & Cipollini, 2008;Kuper, 2002;McAleer, 2010;Xu, Ma, Chen, & Zhang, 2019).…”
Section: Oil Price Volatilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The oil price volatility that occur in a country can affect its exchange rate movements (Babatunde, 2015). Oil commodities, including oil prices and oil exports, have proven a strong long-term integration relationship with several variables including time deposits, demand deposits and gross domestic savings (Aravind & Nayar, 2020). High volatility in oil prices tends to be triggered by increased demand that cannot be met by suppliers, resulting in scarcity both in developed markets and emerging markets (Abdelaziz, Chortareas, & Cipollini, 2008;Kuper, 2002;McAleer, 2010;Xu, Ma, Chen, & Zhang, 2019).…”
Section: Oil Price Volatilitymentioning
confidence: 99%
“…These shocks must be anticipated by the companies and the government in the short and long term to prepare policies dealing with oil fluctuations in the future. According to Aravind and Nayar (2020), the oil price affects the integration of a capital market as the oil is the main and most important source of funding in the financial sector, and it has a long-term relationship with all macroeconomic variables (Filis et al, 2011;Gisser & Goodwin, 1986;Morales, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Oman is an emerging market and an oil-dependent economy that has been hit by a severe low oil price crisis. Arvanid and Nayar (2020) stated that a downward trend in oil prices reduces private investment and raises concerns regarding a potential slowdown in individual and industrial demand, both of which have an impact on effective demand. They found that oil prices in Oman affect multiple macroeconomic variables, including GDP, deposits, net exports, and consumption, in the long run.…”
Section: Introductionmentioning
confidence: 99%